1972
DOI: 10.1159/000180138
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Iron-Dextran through Cuprophane Membrane of a Disposable Coil Dialyser

Abstract: An in vitro study has demonstrated that pharmaceutical iron-dextran (Imferon) does not pass through, nor is it adsorbed on to, the cuprophane membranes (PT 150) of a disposable coil haemodialyser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Our results are consistent to previous in-vitro and in-vivo reports [6-8]. In a 30-minute HD in-vitro study iron dextran removal was determined for HF and HE dialyzers [7].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent to previous in-vitro and in-vivo reports [6-8]. In a 30-minute HD in-vitro study iron dextran removal was determined for HF and HE dialyzers [7].…”
Section: Discussionsupporting
confidence: 91%
“…The greatest amount of iron removed (8%) was observed with a F8 (Fresenius) HF dialyzer [7]. Other investigators utilizing a cuprophane coil dialyzer in-vitro system determined a 0.5% iron dextran removal over 240 minutes [6]. The only in-vivo dialyzability study utilized iron dextran and HE membranes (Terumo 165 cuprammonium dialyzer) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been two in vitro and one in vivo study that describe the removal of iron dextran by hemodialysis. The first in vitro study showed that less than 0.5% of a 50 mg iron dextran dosage was removed during hemodialysis 7 . The other in vitro study showed that the maximum amount of iron dextran removed by hemodialysis was about 8% when a polysulfone F8 dialyzer was used 8 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, no dialyzable iron was found in in vitro experiments within iron saccharate [12] and iron dextran (DexFerrum ® , American Regent) [12]. Other studies have detected less than 0.5% and sometimes up to 8% dialyzable iron in iron dextran (Imferon InFeD ® , respectively) [13,14].…”
Section: Introductionmentioning
confidence: 98%